Tillage and Its Effect on Agricultural Soils: A Quality Index Approach - María de la Luz Xochilt Negrete-Rodríguez; Eloy Conde-Barajas; Guillermo Antonio Silva-Martínez; Gerardo Acosta-García; Humberto Ramírez-Medina; Fabiola Estefanía Tristán-Flores; Héctor Iván Bedolla-Rivera (Agronomy, 2024)
The growing demand for quality food has intensified agricultural practices, thus deteriorating soil fertility. In response, reclamation techniques such as minimum, zero, or no tillage have been applied, especially in the Bajio region of the State of Guanajuato, Mexico. However, a reliable tool to evaluate the effectiveness of these techniques remains elusive. This study evaluated the effect of zero tillage and conventional tillage by developing a Soil Quality Index (SQI) from eight agricultural soils in the Bajio region. A set of 26 physicochemical indicators was used, reducing them by means of principal component analysis (PCA). Subsequently, the SQI methodology called “unified weighted” was applied. The resulting SQIu included key indicators such as C/N, SND, ESP, and Fe. Although significant differences in soil quality were observed among the samples tested, the SQIu was unable to discern soil quality under the different tillage schemes. This may be attributed to the limited application time of zero tillage, which might not be sufficient to achieve significant recovery of SQI indicators. Nevertheless, the SQIu could be useful as a monitoring tool to evaluate the progress of soil recovery under zero tillage, both in the studied area and in similar contexts at the national or international level.